Criminal Investigation Department Of Cianjur Police Resort Services In Providing Support To The Victims Of Human Trafficking - Marty Fitrianty; Chairul Muriman Setyabudi; Riska Sri Handayani (International Journal of Social Service and Research, 2023)
This study motivated by existence case trading people in the police station Cianjur, which is during This often ignored is related giving support to trafficking victims human level police, This like those in the environment Police Cianjur was discovered own problem or gap in protection of humans trafficking victims, who can seen from exists uncertainty in get due rights and support given by the Police Cianjur. Various problems This need reviewed in a way deep order the problem the can resolved. Therefore that, research This addressed For analyze Criminal Investigation Unit services Police Cianjur in giving support towards trafficking victims human.The theory used in study This is theory service public, theory management public, and theory policy public. Research methods This is method study field carried out through approach study qualitative, with type study exploratory, which is next analyzed with technique data reduction, data presentation, and data verification. Research results This show that service protection and provision support to trafficking victims human, police Cianjur can provide service comprehensive medical, psychological, legal, social, and educational. This thing will help victims of trafficking man recover in a way physical and mental, giving protection legal, and helpful they start new life. However, there is a number obstacle like limitations facility medical, stigma against service psychological, slow legal process, social stigma, and limitations access education is also necessary resolved. Therefore the improvement strategy involving services strengthening Work same, provision facilities, training personnel, and campaigns awareness public need implemented.